Correlations between the Derived and Basic Anthropometric Indices in Hypertension among the People at Chitwan District of Nepal - Aryal, Dr. Bijay (International Journal of Pharmaceutical & Biological Archive, 2012)
Correlations between the Derived and Basic Anthropometric Indices in Hypertension among the People at Chitwan District of Nepal